2021
DOI: 10.1063/5.0049105
|View full text |Cite
|
Sign up to set email alerts
|

On the mechanism of ionization oscillations in Hall thrusters

Abstract: Low-frequency ionization oscillations involving plasma and neutral density (breathing modes) are the most violent perturbations in Hall thrusters for electric propulsion. Because of its simplicity, the zero-dimensional (0D) predator–prey model of two nonlinearly coupled ordinary differential equations for plasma and neutral density has often been used for the characterization of such oscillations and scaling estimates. We investigate the properties of its continuum analog, the one-dimensional (1D) system of tw… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 37 publications
0
6
0
1
Order By: Relevance
“…In them, the main attention is paid to the formal construction of mathematical models of fluctuations of plasma parameters in Hall thrusters and mathematical modeling without specific reference to the integral parameters of the thruster -thrust, specific impulse, efficiency. Well-known mathematical models [14][15][16] describe, as a rule, some specific physical mechanism of occurrence of discharge current fluctuations. At the same time, when conducting experimental studies, fluctuations of the discharge current of different character were found, the mechanisms of which may be different.…”
Section: Discussion Of Results Of Investigating Discharge Current Osc...mentioning
confidence: 99%
“…In them, the main attention is paid to the formal construction of mathematical models of fluctuations of plasma parameters in Hall thrusters and mathematical modeling without specific reference to the integral parameters of the thruster -thrust, specific impulse, efficiency. Well-known mathematical models [14][15][16] describe, as a rule, some specific physical mechanism of occurrence of discharge current fluctuations. At the same time, when conducting experimental studies, fluctuations of the discharge current of different character were found, the mechanisms of which may be different.…”
Section: Discussion Of Results Of Investigating Discharge Current Osc...mentioning
confidence: 99%
“…Several instabilities have been identified and studied in HTs. These instabilities cover a large range of frequencies, including: (1) the so-called Breathing Mode (BM) [17][18][19][20] at ≈ 10 kHz, (2) the Ion Transit-Time Instability (ITTI) [21][22][23][24] at ≈ 500 kHz, (3) the Modified Two-Streams Instability (MTSI) [25][26][27][28] at ≈ 1 MHz, (4) the Electron Cyclotron Drift Instability (ECDI) 6,8,15,25,[29][30][31][32][33] and (5) the evolution of the ECDI towards an Ion Acoustic Wave (IAW) 16,27,34 , at ≈ 8 MHz. However, the origin, the growth and the saturation mechanisms of some of the above instabilities remain unclear (see for instance the different theories proposed for the BM 18,19 , or the partial theoretical treatment of the IAW 16 or the ITTI 21 ).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, in the low-frequency range (∼ 10 kHz), the Breathing Mode (BM) is found as a low-frequency ionization instability. Despite the origin of this instability not being fully understood 49,50 , it is commonly accepted that the BM should not be considered among electrostatic plasma instabilities.…”
Section: Introductionmentioning
confidence: 99%